Free Radicals in Aging - Rodrigues, Karen Simona; Besiashvili, Nino (Caucasus Journal of Health Sciences and Public Health, 2020)
Aging is a biological phenomenon concerning all living multicellular organisms. Many studies have been conducted to identify the mechanisms underlying this process. To date, multiple theories have been proposed to explain the causes of aging. One of them is the free radical theory which postulates that reactive oxygen species (ROS), extremely reactive chemical molecules, are the major cause of the aging process. These free radicals are mainly produced by the mitochondrial respiratory chain as a result of electron transport and the reduction of the oxygen molecule. Toxic effects of ROS on cellular components lead to accumulation of oxidative damage which causes cellular dysfunction with age. Aging is characterized by decrements in maximum function and accumulation of mitochondrial DNA mutations, which are best observed in organs such as the brain that contain post-mitotic cells